Outcome of Patients with OA Grade III/IV, with Ligament Laxity Undergoing Proximal Fibular Osteotomy with Lateral Bending Gait and Dextrose 10% Injection : A Case Series - Maulana, Irfan Alfi; Cahyono, Aristida; Hasanah, Lisa Nur (Oshada, 2025)
Knee osteoarthritis (OA) with varus deformity and ligament laxity presents a complex clinical challenge, particularly in patients experiencing chronic pain, joint instability, and functional limitations. While Total Knee Arthroplasty (TKA) remains the gold standard for severe OA, not all patients are willing or have access to this procedure. Proximal Fibular Osteotomy (PFO) has emerged as a minimally invasive and cost-effective alternative, which can be combined with rehabilitative and regenerative approaches to optimize function. This case series reports two female patients aged 55 and 62 years with grade III and IV knee OA, genu varus deformity, and mild-to-moderate ligament laxity, without a history of major trauma. Clinical examination revealed medial compartment pain, limited range of motion (ROM), and knee instability during gait. The patients underwent PFO, followed by lateral trunk lean gait training using video-assisted education and mirror exercises, and intra-articular injection of 10% dextrose to enhance ligament stability. Interventions were conducted over two months with periodic rehabilitation monitoring. Clinical evaluation using the Knee Society Score (KSS), Visual Analog Scale (VAS), and ROM demonstrated significant improvements. KSS scores improved across pain, function, satisfaction, and activity domains. VAS scores decreased from 8 to 2 (Mrs. Ng) and 7 to 1 (Mrs. Su), representing ≥75% pain reduction. ROM increased from 100° to 125° (Mrs. Ng) and 110° to 130° (Mrs. Su). Both patients were able to ambulate without assistive devices within 3–4 weeks; Mrs. Su reported no ongoing complaints, while Mrs. Ng experienced only mild fatigue and calf tension. PFO effectively reduced medial compartment pressure, lateral trunk lean gait modified knee biomechanics, and 10% dextrose supported ligament stability. This multimodal approach is a promising conservative strategy or bridge to TKA, improving function, reducing pain, and enhancing quality of life, particularly in resource-limited settings or in patients refusing TKA..